PENGARUH REVIEW CELEBRITY ENDORSEMENT DAN MEDIA SOSIAL TERHADAP MINAT BELI PADA PRODUK KECANTIKAN “MS GLOW” BY OWNER IBU MARISA DI KOTA TANGERANG - Sugiarti, Rista; Haryantini (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of celebrity endorsement and Instagram social media on purchasing interest in Ms Glow beauty products in shops in Tangerang City. This research is quantitative research. The sample for this research was 97 respondents. The sampling technique uses Probability Sampling with Random Sampling type. According to Sugiyono (2018:118)